People you will hear next week - Unknown:::Creator::::::::::::; Scholes, Percy, 1877-1958:::Contributor:::::::::::: (BBC; London; England)
Illustration and text about Paul Klenau, verso with text by Perry Scholes on pieces in the program, with photographs of the following individuals: Dorothy Silk, Dorothy Howell, Joan Hastings, Reginald Whitehead, William Heseltine, Wynne Ajello, Paul Klenau.